Quality of written forms of informed consent in critically ill patients - Anabel Hernández-Ruiz; Rebeca Iracema Delgado-Fernández; Carlos Omar Mitjans-Fuentes; Rosario González-Volta; Teresa Cuní-Rivera; Denis Díaz-González (Archivo Médico de Camagüey, 2020)
Background: Informed Consent is the acceptance of a medical intervention by a patient, in a free, voluntary and conscious way, after the doctor has informed him of the nature of the intervention, risks, benefits and alternatives. Objective: to assess the quality of structure and content of the informed consent forms in severe patients. Methods: cross-sectional retrospective descriptive study was carried out with 335 IC written forms applied to family members and/or patients admitted to the Intensive Care Unit of the Joaquín Albarrán Domínguez Hospital, Havana, Cuba, from September 30, 2017 to September 22, 2018. The Chi-square test was performed the frequencies of compliance. A value of p ≤ 0.05 was significant. Results: predominantly, the written formats in patients with a clinical profile complied with the completion of the document and the best were those of surgical profile. In compliance with the general data in the IC written format, there was an adequate compliance, in the forms of the clinical profile, they did not comply with writing the name and description of medical procedures. There was no consent forms to authorize medical researches and it was not delivered a copy of the written document to the interested persons. Conclusions: the quality of the formats was bad, we still have to improve the information offered, clarify the doubts, as well as the request for authorization for medical research and implement mechanisms that facilitate the delivery of a copy of the written document.